DEVELOPMENT OF A SUSTAINABLE BUSINESS MODEL FOR DENIM - Shree, Udita; Agarwal Srivastava, Dr. Neelam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Globally, over a billion dollars are spent on denim jeans each year, and that number is still growing. As a result of this expansion, the production of waste in the systems is also increasing. According to the Environmental Protection Agency (EPA), roughly 5% of all landfill space is textile waste, including denim. One of the least ecological industries in the world is the denim industry. This calls for more intensive interventions in the design of sustainable development, as it calls into question the key criteria of sustainability. This topic has been covered by various models of industrial sustainability, although these models focus on solving global problems, assuming small improvements and growth. Consequently, a sustainable business model approach is necessary to drastically rethink how firms should operate to support system-level sustainability. This paper will provide comprehensive background information on the denim business and its operations before offering some notable case studies of well-known companies that use environmentally friendly practices. The result of this document will be a comprehensive analysis and building of a sustainable business model for the denim sector.